2020
DOI: 10.1002/jcc.26159
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐inversion mechanisms in O2 binding to a model heme complex revisited by density function theory calculations

Abstract: Spin‐inversion mechanisms in O2 binding to a model heme complex, consisting of Fe(II)‐porphyrin and imidazole, were investigated using density‐functional theory calculations. First, we applied the recently proposed mixed‐spin Hamiltonian method to locate spin‐inversion structures between different total spin multiplicities. Nine spin‐inversion structures were successfully optimized for the singlet–triplet, singlet–quintet, triplet–quintet, and quintet–septet spin‐inversion processes. We found that the singlet–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
(167 reference statements)
0
14
1
Order By: Relevance
“…We use the standard 6‐311 + G* basis sets for Fe and O atoms, and the 6‐31G** basis sets for C, N, and H atoms, as in our previous work. [ 39 ] The B97D calculations are done at the grid points described by the three coordinates R , θ , and d , where the structure of the PorIm part is taken from the optimized structure of the isolated FePorIm in the lowest quintet state. Twenty‐seven points are used for R in the range of 1.5–6 Å. Eleven points are chosen for θ in the range of 80–150°, whereas 13 points in the range of −0.4–0.4 Å are used for d .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We use the standard 6‐311 + G* basis sets for Fe and O atoms, and the 6‐31G** basis sets for C, N, and H atoms, as in our previous work. [ 39 ] The B97D calculations are done at the grid points described by the three coordinates R , θ , and d , where the structure of the PorIm part is taken from the optimized structure of the isolated FePorIm in the lowest quintet state. Twenty‐seven points are used for R in the range of 1.5–6 Å. Eleven points are chosen for θ in the range of 80–150°, whereas 13 points in the range of −0.4–0.4 Å are used for d .…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, we found that the motion along d was an important role in the quintet-septet and quintet-singlet spininversion processes. [39] The Hamiltonian of the three degrees of freedom model employed in this work is written (in atomic units) as…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations